Assessing the prices and affordability of oncology medicines for three common cancers within the private sector of South Africa - Phyllis Ocran Mattila; Zaheer-Ud-Din Babar; Fatima Suleman (BMC Health Services Research, 2021)
Abstract Background Prices of cancer medicines are a major contributor to the cost of treatment for cancer patients and the comparison of these cost needs to be assessed. Objectives To assess the prices of cancer medicines for the three most common cancers ((breast, prostate and colorectal) in the private healthcare sector of South Africa. Methods The methodology was adapted from the World Health Organization (WHO)/ Health Action International (HAI) methodology for measuring medicine prices. The Single Exit Price (SEP) variations between product types of the same medicine between the highest- and lowest-priced product and between Originator Brand (OB) and its Lowest Priced Generic (LPG) of the same medicine brand was compared, as of March 2020. The affordability of those medicines for cancer usage based on treatment affordability in relation to the daily wage of the unskilled Lowest-Paid Government Worker (LPGW) was also determined. Also, a comparison of the proportion of the population below the poverty line (PL) before (Ipre) and after (Ipost) procurement of the cancer medicines was determined. Results SEP Price differences ranged from 25.46 to 97.33% between highest- and lowest-priced products and a price variation of 72.09% more for the OB than the LPG medicine, except for one LPG that was more expensive than the OB. Affordability calculations showed that All OB treatments for all three cancers (breast, prostate and colorectal), except for paclitaxel 300 mg (0.2 days wage) and Fluorouracil (Fluroblastin) 500 mg (0.3 days wage) costs respectively were more than 1 day’s wage, with patients diagnosed with colorectal cancer needing 32.5 days wages in order to afford a standard course of treatment for a month. Conclusion There was a considerable variation in the price of different brands of cancer medicines available in the South African private sector.